2022
DOI: 10.3389/fnbeh.2022.821080
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Physical and Vicarious Psychosocial Stress Alter Fentanyl Consumption and Nucleus Accumbens Rho GTPases in Male and Female C57BL/6 Mice

Abstract: Chronic stress can increase the risk of developing a substance use disorder in vulnerable individuals. Numerous models have been developed to probe the underlying neurobiological mechanisms, however, most prior work has been restricted to male rodents, conducted only in rats, or introduces physical injury that can complicate opioid studies. Here we sought to establish how chronic psychosocial stress influences fentanyl consumption in male and female C57BL/6 mice. We used chronic social defeat stress (CSDS), or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
2
6
0
Order By: Relevance
“…The effect of fentanyl abstinence alone is less pronounced in the open-field based test because the arena, testing duration, and social target are different from the 3chamber social interaction test. The decreased social interaction we see here in the 3-chamber test is concordant with our previous work showing reduced social interaction in this test after 56 hr of fentanyl abstinence (Franco et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The effect of fentanyl abstinence alone is less pronounced in the open-field based test because the arena, testing duration, and social target are different from the 3chamber social interaction test. The decreased social interaction we see here in the 3-chamber test is concordant with our previous work showing reduced social interaction in this test after 56 hr of fentanyl abstinence (Franco et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Since NAc MSNs are also important for the behavioral response to stress (Fox et al, 2020a), we provided fentanyl in the drinking water to minimize injection and handling stress. Here, and in our other work, we found mice will reliably consume fentanyl water in amounts similar to plain tap water (Franco et al, 2022). Because mice receive fentanyl as they consume water throughout the day, this method has the added benefit of mimicking intermittent drug use (vs continuous exposure) and minimizing repeated bouts of withdrawal between injections.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Remarkably, levels of Nr4a1 and its target genes were not significantly changed in the VP of female mice. Recent work showed that other small GTPases from the Ras superfamily were unaltered by stress and repeated drug intake in the NAc of female mice 50 . This further suggests that drug exposure may differentially involve small GTPases in males and females, possibly through distinct transcription factor activation patterns 16 .…”
Section: Discussionmentioning
confidence: 99%